Depletion of dark matter within globular clusters. (July 2020) - Ardi, E; Baumgardt, H
Abstract: Gravitationally bound group of stars which are identified as globular clusters are known to have a small amount of dark matter. Assuming that globular clusters are formed within dark matter halos, they must have lost significant amount of dark matter. Observations of globular clusters reported flattening velocity dispersion on the outskirt clusters. This could be a sign of existence of dark matter. Theoretically, dynamical processes such as dynamical friction and mass segregation and tidal stripping could be responsible for the depletion of dark matter from the cluster center. Numerical simulations are conducted to follow the evolution of the models of globular clusters composed out of stars and dark matter particles. The results show that the dark matter is depleted from the center of globular clusters due to dynamical friction and mass segregation of stars. An external tidal field from a Milky Way like galaxy effects to deplete the dark matter in the outer part of the clusters. However, within the Hubble time, about 80 % of dark matter's initial values still remain in the outer part of clusters. This might explain the existence of significant amount of dark matter in the outer part of observed clusters.